Usulan Strategi Peningkatan Aspek Aksesbilitas Guna Mempermudah Proses Interview Dengan Pelamar Disabilitas Tunarungu - Pangestu, L Mutiara C; Nurjanah, Siti (STREAMING, 2025)
Currently, many companies do not know about the Deaf disability and do not understand how to implement recruitment procedure for Deaf workers. Because it is difficult to get work everywhere and because of the lack of knowledge regarding the recruitment process for works with disabilities. The aim of this research is to improve strategies for improving accessibility aspects to facilitate the interview process with Deaf applicants. This research was carried out using the Nvivo application using a qualitative approach to interview transcript data so that the results could be known after carrying out interviews with six people. However, the findings concluded that various companies did not provide knowledge or awareness of Deaf disabilities, so they did not seek information about people with disabilities, including Deaf disabilities, which made the interview process with Deaf candidates less smooth.